PENERAPAN MODEL INCREMENTAL PADA IMPLEMENTASI DAN PENGUJIAN SISTEM INFORMASI PENDANAAN USAHA MIKRO KECIL (PUMK): APPLICATION OF THE INCREMENTAL MODEL IN THE IMPLEMENTATION AND TESTING OF SMALL MICRO ENTERPRISES FUNDING INFORMATION SYSTEMS - Halimah, Halimah; Arsa, Daniel; Hutabarat, Benedika Ferdian (Jurnal Sistem Informasi dan Bisnis Cerdas, 2024)
This study implements the Micro Small Business Funding Information System (PUMK) using the incremental model method to enhance the efficiency of managing micro small businesses (MSBs) at PT. Angkasa Pura II Jambi Branch Office. The system was developed based on communication with Angkasa Pura II Jambi Branch Office, followed by testing using black box testing and User Acceptance Testing (UAT). The pre-increment phase involves the identification and analysis of system requirements, which are then designed as the foundation for development. The first increment focused on partner applications and loan cards, while the second increment added features for uploading proof of payment, payment approval, reports, and account management. Coding commenced after the completion of basic data design. The results of black box testing indicate that all functionalities in the second increment operate smoothly without any issues. UAT involved 18 respondents, yielding a system acceptance rate of 88%, suggesting that the implemented PUMK system has been well-received by users. Thus, the implementation of the PUMK Information System using the incremental model method successfully enhances efficiency in managing MSBs, demonstrating effective utilization and favorable user acceptance.